Perbandingan Kadar Hemoglobin, Hematokrit, dan Leukosit Pasien Stroke Infark dan Stroke Perdarahan dengan Covid-19 - Daffa Khairan; Alya Tursina; Mochammad Faisal Afif Mochyadin (UPT Publikasi Ilmiah Unisba, 2024)
Abstract. The highest number of stroke sufferers in 2018 were patients aged 75 years and over as much as 50.2% and the lowest was in the 15-24 year age range, which was equivalent to 0.6%. On the other hand, the Coronavirus disease-19 (COVID-19) pandemic has also recently attracted world attention. This study aims to determine the relationship between hemoglobin, hematocrit, and leukocytes with the incidence of stroke in Covid-19 patients at the Sumedang District Hospital in 2020-2022. The results of hemoglobin, hematocrit and leukocyte examinations are obtained through laboratory examination and are classified into normal or abnormal levels, while the diagnosis of Covid-19 is based on antigen examination. From the research results, it was found that of the 68 samples, the majority of stroke patients with Covid-19 at Sumedang District Hospital in 2020-2022 having an age range of 50-74 years were 47 people (69%). The majority of stroke patients with Covid-19 at Sumedang District Hospital in 2020-2022 were men as much as 37 people (54%). The majority of stroke patients among Covid-19 patients at the Sumedang District Hospital in 2020-2022 had hemoglobin in the range of 12.3-15.3 g/dl, hematocrit levels between 35-47%, and leukocyte levels >10,000 mm3. There is no relationship between hemoglobin, hematocrit and leukocyte levels with the incidence of stroke in Covid-19 patients at Sumedang District Hospital in 2020-2022. Abstrak. Jumlah penderita stroke terbanyak pada tahun 2018 adalah pasien berusia 75 tahun keatas yaitu sebanyak 50,2% dan terendah pada rentang umur 15-24 tahun yaitu setara dengan 0,6%. Di sisi lain, pandemi Coronavirus disease- 19 (COVID-19) juga baru-baru ini menarik perhatian dunia. Penelitian ini bertujuan untuk mengetahui hubungan hemoglobin, hematokrit, dan leukosit dengan kejadian stroke pada pasien Covid-19 di RSUD Kabupaten Sumedang tahun 2020-2022. Penelitian ini menggunakan metode analitik observasional dengan desain cross sectional. Jumlah sample yang diambil sebanyak 68 orang. Dari hasil penelitian didapatkan bahwa dari 68 sampel, pasien stroke dengan Covid-19 di RSUD Sumedang pada tahun 2020-2022 memiliki rentang usia 50-74 tahun yaitu sebanyak 47 orang (69%). Sebagian besar pasien pasien stroke dengan Covid-19 di RSUD Sumedang pada tahun 2020-2022 adalah laki-laki yaitu sebanyak 37 orang (54%). Sebagian besar pasien stroke pada pasien Covid-19 di RSUD Kabupaten Sumedang tahun 2020-2022 memiliki hemoglobin di rentang 12.3-15.3 g/dl, kadar hematokrit antara 35-47%, dan kadar leukosit >10.000 mm3. Tidak terdapat perbandingan yang signifikan pada kadar hemoglobin, hematokrit, maupun leukosit dengan kejadian stroke pada pasien Covid-19 di RSUD Sumedang pada tahun 2020-2022.